All gas-phase synthesis of graphene: Characterization and its utilization for silicon-based lithium-ion batteries. (10th May 2018) - Münzer, Adrian; Xiao, Lisong; Sehlleier, Yee Hwa; Schulz, Christof; Wiggers, Hartmut
Abstract: We report on a gas-phase synthesis method for the preparation of free-standing few-layer graphene in a microwave plasma reactor using pure ethanol as precursor. This scalable synthesis route produces gas-phase graphene (GPG) with lab-scale production rates up to a few hundred mg/h. The physico-chemical properties of the resulting GPG were characterized by XRD, FTIR-, and Raman spectroscopy, electrical conductivity measurements, XPS, and HRTEM in combination with EELS. The materials' properties were compared with those of reduced graphene oxide (rGO) made by the established Hummers' method. The results indicate that the gas-phase synthesis method provides highly-ordered few-layer graphene with extraordinary high purity, very low oxygen content of less than 1 at.%, and high specific conductivity. Both graphene materials were processed in combination with gas-phase synthesized silicon nanoparticles towards silicon-graphene nanocomposites for Li-ion battery anodes. Subsequent electrochemical testing revealed that the gas-phase graphene significantly enhances the long-term stability and Coulomb efficiency of the composite compared to pristine silicon and outperforms the composite fabricated from reduced graphene oxide.